EKO-TEOLOGI PROFETIK: KRITIK SANAD DAN MATAN HADITS-HADITS PELESTARIAN DALAM PERSPEKTIF MAQASID SYARIAH - Annur, Ash Shifa; Jannah, Miftahul (Yayasan An Nur Menara Baro, 2026)
The global ecological crisis demands a theological response that is not only normative but also transformative. This article aims to reconstruct Islamic environmental ethics through takhrij (tracking) and naqd (criticism) of environmental hadiths, and reframing them in the perspective of Maqasid Syariah. This research uses a qualitative method with a mixed-method approach between traditional hadith science (criticism of sanad and matan) and contemporary Islamic legal hermeneutics. The focus of the study is the hadith on planting trees (ghars) and the revitalization of dead land (ihya’ al-mawat). The results of the study indicate that: (1) The hadith narrated by Anas bin Malik about planting trees has authentic status with a muttasil (continuous) transmission line and is free from syadz (oddities); (2) In terms of matan, the hadith contains futuristic content that goes beyond merely eschatological dimensions, but also ethical commands for resource sustainability; (3) From the perspective of Maqasid Syariah, environmental preservation (hifz al-bi’ah) must be placed on a par with the protection of the soul (hifz al-nafs), because ecological damage fundamentally threatens human existence. This article concludes that prophetic eco-theology offers a solid spiritual foundation for modern sustainability policies.